2016
DOI: 10.1007/s00414-016-1467-4
|View full text |Cite
|
Sign up to set email alerts
|

New models for age estimation and assessment of their accuracy using developing mandibular third molar teeth in a Thai population

Abstract: Age estimation using developing third molar teeth is considered an important and accurate technique for both clinical and forensic practices. The aims of this study were to establish population-specific reference data, to develop age prediction models using mandibular third molar development, to test the accuracy of the resulting models, and to find the probability of persons being at the age thresholds of legal relevance in a Thai population. A total of 1867 digital panoramic radiographs of Thai individuals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 36 publications
0
19
0
2
Order By: Relevance
“…In addition to bones, teeth have been reported to have a good correlation with age in Thai populations. Duangto et al, in 2017, investigated third molars, and found high accuracy in their ability to predict age for both males and females (Duangto et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to bones, teeth have been reported to have a good correlation with age in Thai populations. Duangto et al, in 2017, investigated third molars, and found high accuracy in their ability to predict age for both males and females (Duangto et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Chronological age anticipation is significant, especially at the age of 18, when legal procedures come into effect in Thailand. In Thailand, the Criminal Code states that "For any person over 15 years of age but not yet 18 years of age, it shall reduce the scale of punishment as provided for such offense by one -half (section 75)" [9]. Therefore, the accuracy of age estimation methods for suspects with unknown chronological age is needed in the interest of justice [10].…”
Section: Discussionmentioning
confidence: 99%
“…Similar a nuestro estudio, donde el coeficiente de correlación para la pieza 3.8 en el sexo femenino fue de 0,8817 y en el sexo masculino de 0,915, con respecto a la pieza 4.8 en el sexo femenino la correlación fue de 0,8844 y en el sexo masculino de 0,955. 13 Venkatesh y Vishwanath en su estudio realizado en el año 2016, conjunto con el estudio realizado por Kasper y colaboradores, concluyeron que las etapas de desarrollo del tercer molar son útiles y fiables en la estimación de la edad dental, y no encontraron diferencias significativas entre los sexos para los cuatro terceros molares, evidenciando que todos los individuos que presentaban el tercer molar maduro tenían al menos 18 años de edad. 10,14 En el año 2012, Li realizo un estudio en adolescentes chinos occidentales; donde examinó un total de 2078 radiografías panorámicas digitales, de 989 hombres y 1089 mujeres entre 5 y 23 años, observando que el desarrollo de terceros molares en la población china occidental era probable que comience a la edad de 5 años, resultados que difieren con el presente estudio, ya que el desarrollo de mineralización de la pieza 3.8 en las mujeres comienza a los 9,15 años ± 0,96 (estadio A), y en los hombres a los 10,00 años ± 1,36 (estadio A); para la pieza 4.8 el proceso de mineralización inicia a los 9,50 años ± 1,53 (estadio A) en las mujeres, y a los 10,00 años ± 1,36 (estadio A) en los hombres.…”
Section: Discussionunclassified